Alternatif Untuk Meminimalisasi terhadap Pelanggaran HAM dalam Penegakan Hukum Pidana - Ryan Aditama (Universitas Batanghari Jambi, 2020)
Related to the general provisions of Law No. 39 of 1999 concerning Human Rights, which states that the beginnings of the history of the Indonesian nation to date have recorded various problems including: suffering, misery and social inequality, resulting from unjust and discriminatory acts and actions on ethnic, racial, cultural understanding, language, color, skin, and religion, as well as class, gender, and even social status and others. These unjust and discriminatory acts are included in violations of human rights, both vertically